2001
DOI: 10.1053/jhep.2001.25759
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection and Needle Exchange Use Among Young Injection Drug Users in San Francisco

Abstract: Young injection drug users (IDUs) in San Francisco may be at high risk for hepatitis C virus (HCV) infection despite access to several needle exchange venues. The authors conducted a cross-sectional study from 1997 to 1999 in San Francisco to estimate the prevalence and incidence of antibody to HCV (anti-HCV) among street-recruited IDUs under age 30, and to examine risk behaviors and sources of sterile needles. Among 308 participants, the prevalence of anti-HCV was 45%. Using statistical modeling, incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
119
1
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 51 publications
10
119
1
6
Order By: Relevance
“…Such characteristics correspond to those found in other reports (Cobos Calleja et al 2003). The data and analysis shown here were restricted to males, which make up the majority of the drug-using population in many report (Hahn et al 2001, Cobos Calleja et al 2003.…”
Section: Discussionsupporting
confidence: 90%
“…Such characteristics correspond to those found in other reports (Cobos Calleja et al 2003). The data and analysis shown here were restricted to males, which make up the majority of the drug-using population in many report (Hahn et al 2001, Cobos Calleja et al 2003.…”
Section: Discussionsupporting
confidence: 90%
“…Nowadays, the concept of blood transfusion as a risk factor for both viruses has almost disappeared due to the introduction of serological tests in the 80´s, besides syringe exchange programs and educational programs implemented in major cities, originally as an immediate reaction to AIDS epidemy 9,18,25 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Older age and longer injecting duration could account for the higher upper bounds of these estimates; however, two U.S. studies 8,9 reported finding 33 and 36 % of IDUs under 25 years old were HCV infected and several non-U.S. studies found a much higher prevalence even among IDUs in this age group. 10 In 2007, 48 % of individuals with incident HCV in the U.S. reported injection drug use, which continues to be the leading risk factor for infection.…”
Section: Introductionmentioning
confidence: 99%